Pengaruh Jenis Pelarut pada Metode Microwave Assisted Extraction (MAE) terhadap Karakteristik Ekstrak Daun Singkong (Manihot utilissima Pohl.) - Wahyuni, Yustika Ayu Tri; Kadek Diah Puspawati, Gusti Ayu; Kencana Putra, I Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 4 (2021): Jurnal ITEPA, 2021)
Cassava leaf has bioactive components, such as flavonoids and chlorophyll pigments, but the information on cassava leaf extract is still limited and needs development on the using extraction method of microwave. The type of solvent is an important factor in the success of extracting the material. This research was conducted to determine the effect of the solvent using Microwave Assisted Extraction (MAE) method on the characteristics of cassava leaf extract (Manihot utilissima Pohl.) and to find the right type of the solvent using Microwave Assisted Extraction (MAE) to produce the best cassava leaf extract. The research design used was a Completely Randomized Design with a solvent type treatment consisting of five types of solvents, namely aquades, ethanol 90%, acetone 90%, methanol 90%, and ethyl acetate 90%. The treatment was repeated three times to obtain 15 experimental units. The data obtained were analyzed by the analysis of variance and if the treatment had a significant effect to variable observed, it was continued with Duncan’s Multiple Range Test. The parameters observed in this study were yield, total chlorophyll content, total flavonoids content, antioxidant activity, IC50, and L*, a*, b* values. The result showed that the type of solvent had a very significant effect (P<0,01) on yield, total chlorophyll content, total flavonoids, antioxidant activity, IC50, and L*, a*, b* values. The best treatment was found in ethanol 90% which produced a yield 19.84%, total flavonoids 74.90 mg QE/g, total chlorophyll 9.98 mg/g, antioxidant activity 83.67%, and L*: 44.83, a*: -9.97, b*: 20.27.